PENGGUNAAN MEDIA BARU PADA PEMBANGUNAN PARIWISATA BATURRADEN ADVENTURE FOREST BERBASIS ECOTOURISM - Hanif Adhiyatmika; Adhi Iman Sulaiman; Shinta Prastyanti (KINESIK, 2022)
The development of ICT has begun to enter various sectors, including the tourism industry. So to increase tourism development with ICT is an effective way why is that because the percentage of internet users has a positive and significant influence on the added value of the tourism sector. Therefore, we will see what Baturraden Adventure Forest (BAF) looks like as ecotourism-based tourism using ICT. Seeing how BAF uses ICT as a tool to promote or market BAF via the internet, we can do a descriptive analysis using The 7C Framework from Rayport and Jaworski. communication, connection, and commerce.